Association Study in Selected Genotypes of Rice (Oryza sativa L.) under Irrigated Rainfed and Terminal Stage Drought conditions - Rawte, Suman; Saxena, Ritu R.; Toppo, NeerajAnkur; Kulhariya, Saurabh Kumar (International Journal of Bio-resource and Stress Management, 2020)
The growth and productivity of rice is adversely affected by water scarcity. Water stress is a limiting factor in agriculture production by preventing a crop from reaching the genetically determined theoretical maximum yield. Association studies among thirteen traits for grain yield were studied in sixty lines of rice during kharif (June-December), 2017 and 2018 at IGKVV, Raipur Chhattisgarh. The materials were selected among from the 400 rice core group which represents the entire diversity. In plants, a better understanding of the morphological and physiological basis of changes in water stress resistance could be used to select or create new varieties of crops to obtain a better performance under water stress conditions. So, the result of correlation coefficient depicts that biological yield and harvest index showed positive association with grain yield under all the condition on the basis of pooled data of two years. On the contrary, days to 50% flowering showed negative but significant correlation with grain yield under stress condition only this suggests that due to differences in rainfall pattern and water scarcity the flowering get delayed hence, the yield is reduced. Considering the result of path analysis based on the pooled data of Kharif, 2017 and 2018 number of filled grains and total number of grains were found to have positive and high direct effect on grain yield under all the conditions, it signifies true relationship with grain yield and selection for above mentioned trait could be good for yield improvement under stress as well as non-stress environment.